2017
DOI: 10.3389/fnins.2017.00298
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Different Degrees of Iodine Deficiency during Pregnant and Lactation Impair the Development of Cerebellar Pinceau in Offspring

Abstract: Aims: Iodine is critical for synthesis of thyroid hormones (TH). And iodine deficiency (ID) is one of the most significant reasons of intellectual disability and motor memory impairment, although the potential mechanisms are still under investigation. Presently, mild ID and marginal ID are largely ignored problems for women of child bearing age. Mild ID is a subtle form of TH deficiency, which shows low levels of free thyroxine (FT4) and relatively normal free triiodothyronine (FT3) or thyroid stimulation horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…A meta-analysis showed mild iodine de ciency was associated with the increase levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyroglobulin antibody (TgAb) in pregnant women, and mild iodine de ciency might elevate the risk of thyroid dysfunction in pregnant women [6] . Dong J's study showed that the alteration of development and maturation in cerebellar pinceau in the offspring were observed following maternal marginal and mild iodine de ciency [7] . However, some studies showed that mild iodine de ciency in pregnant women was not obvious to themselves or their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed mild iodine de ciency was associated with the increase levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyroglobulin antibody (TgAb) in pregnant women, and mild iodine de ciency might elevate the risk of thyroid dysfunction in pregnant women [6] . Dong J's study showed that the alteration of development and maturation in cerebellar pinceau in the offspring were observed following maternal marginal and mild iodine de ciency [7] . However, some studies showed that mild iodine de ciency in pregnant women was not obvious to themselves or their offspring.…”
Section: Introductionmentioning
confidence: 99%